215 Examining the Benefits of One-To-One African Caribbean Mentoring for Prospective Medical Students. (19th August 2022) - Carey, C; Jordan, C; Wheatle, M; Edward, S
Abstract: Aim: African Caribbean people are underrepresented in UK medical schools. African Caribbean Medical Mentors (ACMM) is a UK registered charity that provides one-to-one mentoring to prospective African Caribbean medical students. Mentors consist of current African Caribbean medical students and doctors. This study aimed to investigate the specific benefits provided by ACMM and the attributes of successful mentoring relationships. Method: Participants were identified using ACMM's database of mentees and mentors enrolled within the last 3 years and an online questionnaire was distributed via Qualtrics. Questions were scored on a scale between 1 and 10 and participants were asked to explain their rankings. Results: 11 mentees and 7 mentors responded to the surveys. 63.6% and 72.7% of mentees gave a score between 8 – 10 regarding the importance of having a mentor and having a mentor that was African Caribbean respectively. All mentees reported satisfaction with their mentor, with 45.5% citing individualised interview practice and 63.6% reporting mentor support and availability as positive aspects of their mentoring relationship. All mentors reported being satisfied with the program, with 57.1% and 71.4% giving a score between 8 – 10 regarding the importance of having a mentor and having a mentor that was African Caribbean respectively. 42.9% of mentors reported that improved methods and proactivity with communication could have improved their mentoring relationship. Conclusion: This study suggests that one-to-one mentoring between African Caribbean mentors and mentees was helpful during medical school applications. Interview practice proved particularly useful, whilst methods and timescales of communication represent areas for improvement.